Willow - Howard, Ron, 1954-; Davis, Warwick; Kilmer, Val, 1959-2025; Whalley-Kilmer, Joanne; Horner, James (Beverly Hills, CA : Twentieth Century Fox Home Entertainment, 2001)
A dwarf is entrusted to take the baby princess to safety and is joined by a swordsman who helps him battle the forces of evil who want to kill the child.
Originally released as a motion picture in 1988.
Features: audio commentary, featurettes, behind-the-scenes, trailers, TV spots.
Director of photography, Adrian Biddle ; production design, Allan Cameron ; editors, Daniel P. Hanley, Mike Hill ; music, James Horner.
Warwick Davis, Val Kilmer, Joanne Whalley, Jean Marsh, Billy Barty.
MPAA rating: PG.
DVD, Dolby digital 5.1 and surround.
Keywords: Video recordings for hard of hearing people; Feature films; Action and adventure films; Fantasy films